Ujrah and Services Analysis of Gold Pawn Customer Satisfaction at Mandiri Syariah Bank of Palopo City - Andi Tenri A. Zulkarnain (Journal Of Institution And Sharia Finance, 2021)
The aims of this research are: to determine the effect of ujrah and pawn gold customer service simultaneously on satisfaction at Bank Syariah Mandiri, Palopo City; The type in this research is quantitative. Then the population is 1949 customers who have pawned their gold at Bank Syariah Mandiri Palopo. Sampling In this study, Simple Random Sampling will be used (a simple random technique), namely a sampling technique that provides equal opportunity to the population to be sampled. Then the sample used is using the slovin formula so that the sample is 95 customers who use gold pawn products. The instrument used is a questionnaire (questionnaire). The data analysis technique used is multiple regression. The research results obtained are: 1) partially/t test, it is known that the ujrah variable (X1) has a calculated t value (4.165) and the service variable (X2) has a tcount value (5.848), while the t table value (1.986), so that it can be concluded that ujrah has a positive effect on the Y variable (customer satisfaction) is positive, and service (X2) has a positive effect on the customer satisfaction variable (Y) has a positive value. 2) Simultaneously the variable ujrah (X1) and service (X2) (test f) f count is 37.239 while f table is 3.09 (see table f), because f count > f table (37.239 > 3.09) or significance value of 0.000 <0.05 then H0 is rejected H1 is accepted. So it can be concluded that the ujrah and service variables simultaneously influence the satisfaction of gold pawn customers at Bank Syariah Mandiri, Palopo City.